Empowering Social Studies Education: The Role of M-learning in Fostering Motivation and Well-being - Qolamani, Khalid Ilias Basheer; Abdullah, Saman Ahmed; Rajab Rekani, Mohammed Qais (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Mobile learning (m-learning) offers new possibilities for enhancing motivation and well-being in social studies education. This literature review synthesizes current research on using mobile technologies in K-12 and higher education social studies contexts. Systematic searches yielded 37 empirical studies that were analyzed. Findings indicate emerging interest in m-learning for active learning opportunities leveraging mobile affordances. Student motivation may be increased through engagement, personalization, and bridging formal/informal learning. Well-being can potentially improve via reduced anxiety, social connections, and flow states. However, equitable access, teacher training, privacy, assessment, and curriculum integration require consideration. Gradual implementation, aligning activities to objectives, and promoting digital citizenship are advised. More rigorous research is needed to establish impacts on higher-order thinking and competencies. Harnessed effectively, mobile devices may reinvigorate social studies by connecting school to students’ lives.